2017
DOI: 10.1111/jfpe.12639
|View full text |Cite
|
Sign up to set email alerts
|

Jaboticaba byproduct encapsulation by lyophilization: pH and food application stability

Abstract: The study aimed to microencapsulate jaboticaba byproduct extract by lyophilization, followed by the characterization, pH stability and food application of the prepared microcapsules. The products were visualized by scanning electron microscopy and the yield, encapsulation efficiency (EE%), and bioactive compounds (high‐performance liquid chromatography) were determined. The major compounds found (in all samples) were cyanidin‐3‐glucoside, acids ellagic and gallic, and quercetin. The EE% was 80.0% and yield 67.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In previous studies, it has been reported that the lyophilization technique has significantly benefited in preserving phenolic compounds, color pigments (anthocyanins, carotenoids, etc. ), ascorbic acid, aroma components, and textural properties in fruits and vegetables (Bhatta et al., 2020; Gümüşay, Borazan, Ercal, & Demirkol, 2015; Palacios, Guillamón, García‐Lafuente, & Villares, 2014; Rajkumar et al., 2017; Rodrigues, Dos Santos, Bergamasco, & Madrona, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, it has been reported that the lyophilization technique has significantly benefited in preserving phenolic compounds, color pigments (anthocyanins, carotenoids, etc. ), ascorbic acid, aroma components, and textural properties in fruits and vegetables (Bhatta et al., 2020; Gümüşay, Borazan, Ercal, & Demirkol, 2015; Palacios, Guillamón, García‐Lafuente, & Villares, 2014; Rajkumar et al., 2017; Rodrigues, Dos Santos, Bergamasco, & Madrona, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Microcapsules samples presented around 50% of value in analyses of TPC, TF, DPPH, ABTS and FRAP, as expected. The literature showed than microencapsulation with maltodextrin is efficient for the protection of the bioactive compounds against light, temperature and pH (Ozkan et al 2019, Rodrigues et al 2018a. Also, the spray drying technique has a great impact on the encapsulation characteristics including stability (Santos et al 2019(Santos et al , 2017a.…”
Section: Antioxidant and Color Analysesmentioning
confidence: 99%